2015
DOI: 10.1007/s40271-015-0136-x
|View full text |Cite
|
Sign up to set email alerts
|

Patient Preferences for Injectable Treatments for Multiple Sclerosis in the United States: A Discrete-Choice Experiment

Abstract: Background and ObjectivePatients’ perceptions and experiences of medication efficacy, medication adverse events, dosing frequency, and dosing complexity have been found to influence adherence to injectable disease-modifying treatments (DMTs) in patients with multiple sclerosis (MS). The aim of this study was to quantify patient preferences for features of injectable DMTs for MS.MethodsAdult patients in the United States (US) with a self-reported diagnosis of MS completed an online discrete-choice experiment su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
30
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 42 publications
7
30
0
2
Order By: Relevance
“…These results suggest, that patients do differentiate between injectable treatments based on injection frequency. This is consistent with data presented in previous studies [Poulos et al 2015;Shingler et al 2013;Utz et al 2014;Wicks et al 2015]. The change in injection time was not shown as being important to patients compared with the other attributes studied.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results suggest, that patients do differentiate between injectable treatments based on injection frequency. This is consistent with data presented in previous studies [Poulos et al 2015;Shingler et al 2013;Utz et al 2014;Wicks et al 2015]. The change in injection time was not shown as being important to patients compared with the other attributes studied.…”
Section: Discussionsupporting
confidence: 92%
“…As expected, patients preferred an improvement in outcomes for each attribute, which is consistent with the results of previous DCE studies [Johnson et al 2009;Shingler et al 2013;Poulos et al 2015;Utz et al 2014;Wicks et al 2015;Wilson et al 2014Wilson et al , 2015.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…[3][4][5]9,10 The results of this study suggest that patients with different treatment histories and different levels of disability may place more emphasis on different features of medicines. In addition, given the problems with adherence, new DMTs with alternative routes of administration and dosing frequencies-such as less frequent IV infusions-may provide an alternative that will improve adherence.…”
Section: Figure 4 Self-injectable Treatment Subgroups: Relative Impomentioning
confidence: 82%
“…In all the GLP-1RA studies, a once-weekly dosing regimen was consistently preferred over a once-daily dosing regimen [30, 31, 36, 37, 46, 47]. Interestingly, DCE studies in patients with another chronic disease (multiple sclerosis; MS) also found that the frequency of injections was an important driver of preference for injectable MS treatments [48, 49]. …”
Section: Discussionmentioning
confidence: 99%